Resistance Pattern of Anti-TB Drugs in Drug-Resistant TB of Pulmonary Tuberculosis Patients in Dr. Soetomo Academic Hospital, Surabaya, Indonesia - Marsha Maritsa, Olivia; Mertaniasih, Ni Made; Permatasari, Ariani; Kusmiati, Tutik (Institute of Topical Disease Universitas Airlangga, 2025)
Pulmonary tuberculosis is an infectious disease that can be transmitted through the air due to infection with Mycobacterium tuberculosis bacteria. According to the WHO, TB is the second-highest cause of death in infectious diseases in the world. This study aims to determine patterns of anti-TB drug resistance in drugresistant TB patients in Dr. Soetomo Academic Hospital from January 2022 to December 2023. This was a descriptive retrospective using patient medical record data in Dr. Soetomo Academic Hospital for the period January 2022 - December 2023. This study included 261 drug resistant pulmonary TB patients, the majority of whom were new TB patients (61.3%). Anti-TB drug resistancewas most prevalent in RR-TB (43.7%), with the highest number of new cases (28.4%). Drug susceptibility test showed High-dose Isoniazid (INHHD) had a high resistance rate (56%). Isoniazid (H) had a high resistance rate (66%). Pyrazinamide (Z) showed high sensitivity (66%). Levofloxacin (Lfx) showed high sensitivity (89%). High-dose Moxifloxacin (MfxHD) high sensitivity level (94%). Moxifloxacin (Mfx) high sensitivity level (92%). Bedaquiline (Bdq) high sensitivity level (98%). Linezolid (Lzd) high sensitivity level (99%). Clofazimine (Cfz) high sensitivity level (97%). Amikacin (Amk) high sensitivity level (100%). Drug-resistant pulmonary TB patients recently show a high drug sensitivity pattern to the second-line anti-TB drugs. MTB has become resistant to Isoniazid. However, it is still sensitive to Pyrazinamide by 66% and Levofloxacin by 89%. Moxifloxacin, Bedaquilin, Linezolid, Clofazimine, and Amikacin have high sensitivity >90%.